2010
DOI: 10.1002/cmdc.200900502
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Mediate Differential Responses in Keratinocytes and Fibroblasts during Skin Wound Healing

Abstract: With advances in nanotechnology, pure silver has been recently engineered into nanometer-sized particles (diameter <100 nm) for use in the treatment of wounds. In conjunction with other studies, we previously demonstrated that the topical application of silver nanoparticles (AgNPs) can promote wound healing through the modulation of cytokines. Nonetheless, the question as to whether AgNPs can affect various skin cell types--keratinocytes and fibroblasts--during the wound-healing process still remains. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
182
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(198 citation statements)
references
References 38 publications
(30 reference statements)
14
182
2
Order By: Relevance
“…5 AV and AgNPs alone or in combination increased the number of activated fibroblasts and mature vascular endothelial cells at the 3rd day. This result is in agreement with Liu et al, 36 who reported that AgNPs enhanced fibroblast transformation into myofibroblast. Similarly, Liu et al, 37 found that AV increased fibroblast proliferation and collagen synthesis, and elevated hyaluronic acid and hydroxyproline level, which suggest a possible role in the extracellular matrix remodeling during wound healing.…”
Section: Discussionsupporting
confidence: 93%
“…5 AV and AgNPs alone or in combination increased the number of activated fibroblasts and mature vascular endothelial cells at the 3rd day. This result is in agreement with Liu et al, 36 who reported that AgNPs enhanced fibroblast transformation into myofibroblast. Similarly, Liu et al, 37 found that AV increased fibroblast proliferation and collagen synthesis, and elevated hyaluronic acid and hydroxyproline level, which suggest a possible role in the extracellular matrix remodeling during wound healing.…”
Section: Discussionsupporting
confidence: 93%
“…According to Sibbald et al (2007) the use of silver nanoparticles dressing on a variety of chronic non-healing wounds has a beneficial effect of protecting the wound site from bacterial contamination. Similarly, Liu et al (2010) proved that silver nanoparticles could promote wound healing through facilitating the proliferation and migration of keratinocyte.…”
Section: Wound Dressingmentioning
confidence: 98%
“…Fact based prime level research propounded that large size AgNps causes chondrosomic respiratory chain autophagy and for that regenerate oxygen sensory genus tension [2][3][4][5][6][7][8][9]. Vertebrate primate affecting bacterial stem cells are evidenced to be disrupted by bigger size AgNps and have the capability to arise demolition of reproductive, digestion activities [10]. Still today some specific in-vivo experiments done and the results showed bigger size AgNps have very serious impacts on human being like mal nutrition, atrophy and respiratory ailments which may lead to fatal condition [11,12] this category particles also evokes oxygen sensory genus tension with programmed cell death consequence [13][14][15] and essential amino acids with proteins demarcated at hypovalemic shock stage due to malnutrition [16].…”
Section: Journal Of Nutritional Disorders and Therapymentioning
confidence: 99%